DL0805-2, a novel indazole derivative, relaxes angiotensin II-induced contractions of rat aortic rings by inhibiting Rho kinase and calcium fluxes - Yuan, Tian-yi (Acta Pharmacol Sin, 2016)
AIM: DL0805-2 [N-(1H-indazol-5-yl)-1-(4-methylbenzyl) pyrrolidine-3-carboxamide] is a DL0805 derivative with more potent vasorelaxant activity and lower toxicity. This study was conducted to investigate the vasorelaxant mechanisms of DL0805-2 on angiotensin II (Ang II)-induced contractions of rat thoracic aortic rings in vitro. METHODS: Rat thoracic aortic rings and rat aortic vascular smooth muscle cells (VSMCs) were pretreated with DL0805-2, and then stimulated with Ang II. The tension of the aortic rings was measured through an isometric force transducer. Ang II-induced protein phosphorylation, ROS production and F-actin formation were assessed with Western blotting and immunofluorescence assays. Intracellular free Ca(2+) concentrations were detected with Fluo-3 AM. RESULTS: Pretreatment with DL0805-2 (1–100 μmol/L) dose-dependently inhibited the constrictions of the aortic rings induced by a single dose of Ang II (10(−7) mol/L) or accumulative addition of Ang II (10(−10)–10(−7) mol/L). The vasodilatory effect of DL0805-2 was independent of endothelium. In the aortic rings, pretreatment with DL0805-2 (1, 3, and 10 μmol/L) suppressed Ang II-induced Ca(2+) influx and intracellular Ca(2+) mobilization, and Ang II-induced phosphorylation of two substrates of Rho kinase (MLC and MYPT1). In VSMCs, pretreatment with DL0805-2 (1, 3, and 10 μmol/L) also suppressed Ang II-induced Ca(2+) fluxes and phosphorylation of MLC and MYPT1. In addition, pretreatment with DL0805-2 attenuated ROS production and F-actin formation in the cells. CONCLUSION: DL0805-2 exerts a vasodilatory action in rat aortic rings through inhibiting the Rho/ROCK pathway and calcium fluxes.